Late Quaternary changes of the oxygen conditions in the bottom and intermediate waters on the western Kamchatka continental slope, the Sea of Okhotsk. (March 2016) - Matul, A.; Abelmann, A.; Khusid, T.; Chekhovskaya, M.; Kaiser, A.; Nürnberg, D.; Tiedemann, R.
Abstract: Microfossil data on the foraminifers and radiolarians in the sediment core KOMEX LV28-44-3, the Kamchatka slope in the eastern Sea of Okhotsk, exhibit the changes in the water oxygen conditions during the last 146 ky. The paleoenvironmental proxies are the radiolarian species Cycladophora davisiana as indicator of the upper intermediate water ventilation, and the benthic/planktonic foraminifers as indicators of the bioproductivity and bottom water oxygenation. In case of sediment core LV28-44-3, the bottom water represents the lower intermediate one, so that conclusions on paleoenvironments are applicable for the most range of the local intermediate water. The well-oxygenated intermediate and near-bottom waters existed in the area of study during the penultimate glaciation of MIS 6, Early Weichselian initiation of the last glaciation within MIS 5b–d, and last glacial stages of MIS 3–2. The intervals of the short low-O2 bottom events with suboxic conditions (dissolved O2 in water 0.3–1.2 ml/l) occur during the last interglacial MIS 5e (Eemian stage) 125 to 113 ka, and during the last deglaciation 17.5 to 6.5 ka. Eemian low-O2 bottom events are associated with the high bioproductivity of the subsurface water but poor ventilation on the upper intermediate depths. The low-O2 bottom events during the last deglaciation occurred at the high bioproductivity of the subsurface water and active ventilation on the upper intermediate depths.